Government Culture in Public Services Based On Electronic Government in DKI Jakarta Province - Suprapto, Suprapto; Hamdi, Muchlis; Nurdin, Nurliah; Sinurat, Marja (Budapest International Research and Critics University, 2022)
The implementation of the E-Government system is also driven by a situation that requires the government to reduce waste in financing/expenditures, increase efficiency, meet community expectations, and facilitate economic development. The use of internet technology in government can reduce interactions and direct human-to-human transactions, especially between the state apparatus as service providers and the public as service recipients. Reducing face-to-face interactions means reducing the potential for abuse of authority, such as corrupt and collusive practices. The results of the study indicate that the Smart City program includes the application of E-Government in public services or an integrated citizen administration service system to improve service quality so that citizens can enjoy faster, easier service and the citizen data base can be maintained and updated on an ongoing basis. The Electronic-Based Government System is also included in the list of Regional Strategic Activities (KSD) in 2020. Regional Strategic Activities, hereinafter abbreviated as KSD, are activities that have a strategic nature and/or other activities that have a significant impact on meeting basic needs, accelerating economic growth, and increasing economic growth public welfare. The conclusion is that DKI Jakarta province still adheres to the bureaucratic paradigm (conventional culture). The orientation is still on production cost-efficiency so that service time is still limited to office hours, not yet 24 hours x 7 days. Process Organization still uses functional approach, departmentalization, and control hierarchy. The management principle is still oriented to rule and mandate so that staff and unit leaders do not dare to take a breakthrough for service improvement. This management principle is related to the leadership style which is still command and control so that the space for creativity and innovation becomes narrow. The communication developed has begun to adopt digital era communication by providing a number of communication channels, but it has not been directly connected to the service website. Service delivery for services handled only by PTSP has adopted ICT, but services that involve other OPDs, some of which are still under the conventional paradigm, require applicants to submit physical documents.